2016
DOI: 10.1680/jgein.15.00051
|View full text |Cite
|
Sign up to set email alerts
|

Geogrid pullout load–strain behaviour and modelling using a transparent granular soil

Abstract: The paper describes the results of a series of geogrid pullout tests that were carried out in a novel large pullout box with a transparent granular soil. The test apparatus and methodology allows the entire geogrid specimen to be visible through the bottom of the box. Specimen displacements are computed from image analysis of pictures taken through the transparent bottom of the pullout box during each test. The geogrid material was an integral punched and drawn biaxial polypropylene geogrid. A series of refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…In reinforcement engineering, the interface action characteristic of reinforced soil is the key technical index [5] that directly determines the stability of the reinforcement engineering. In 1974, Schlosser and Long first used triaxial tests to study the mechanical properties of reinforced sand.…”
Section: Introductionmentioning
confidence: 99%
“…In reinforcement engineering, the interface action characteristic of reinforced soil is the key technical index [5] that directly determines the stability of the reinforcement engineering. In 1974, Schlosser and Long first used triaxial tests to study the mechanical properties of reinforced sand.…”
Section: Introductionmentioning
confidence: 99%
“…in the case of a rigid GGR. Theoretical considerations as well as carefully analyzed experiments have clearly shown that in the case of polymeric GGR this assumption is not valid (Sieira et al 2009;Ziegler and Timmers 2004;Bathurst and Ezzein 2016;Wilson-Fahmy et al 1994;Ezzein and Bathurst 2014). The displacement of the transverse ribs and thus the mobilization of the soil resistance is nonlinearly distributed over the length of the embedded GGR.…”
Section: Rigid Ggrmentioning
confidence: 99%
“…The extent to which friction and bearing resistance are mobilized along the GGR depends on how stiff the longitudinal ribs are and whether the junction can sustain the loading, Fig. 1, (Sieira et al 2009;Ziegler and Timmers 2004;Müller 2011;Jacobs et al 2014Jacobs et al , 2016Bathurst and Ezzein 2016). (In this paper the terms "flexible" and "stiff" or "rigid" refer to the stress-strain behavior of longitudinal ribs and not the flexural rigidity of the entire GGR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com a evolução e o desenvolvimento da instrumentação, novos dados puderam ser coletados como as tensões normais e deformações, utilizando células de pressão (geralmente aplicadas abaixo da geocélula) e strain gauges (fixado em suas paredes) (DASH; RAJAGOPAL; KRISHNASWAMY, 2007;MENESES, 2004;ZHOU;WEN, 2008). Mais recentemente, o uso de solos transparentes (ISKANDER, 2010) vem sendo estudado para a análise de ensaios de carregamento em placa em solos reforçados com geossintéticos, incluindo geocélulas (BATHURST; EZZEIN, 2016;NELSEN, 2018;NELSEN;ZORNBERG, 2020;ZIEGLER;DERKSEN, 2019). 2019).…”
Section: Estudos Com Geocélulas Em Pavimentação E Reforço Em Fundaçõesunclassified